Agreement with weight-neutral compared to weight-centric physical activity messages and relationships to sedentary behavior, physical activity, and internalized weight bias in people living in larger bodies - Tanya R. Berry; Maxine M. Myre (Health Literacy and Communication Open)
Background Many anti-obesity health promotion campaigns focus on physical activity as a means to lose weight. Organizations have created positive images of people living with obesity being physically active with the intention of normalizing people in larger bodies being active. However, it is not clear if using the images when taking a weight-neutral (compared to a weight-centric) approach will be more positively received, and thus more effective, in promoting physical activity to people living in larger bodies.Aims The primary purpose of the present research was to examine whether people in larger bodies preferred messages that featured images of people in larger bodies being active with weight-neutral (i.e., no mention of weight loss) compared to weight-centric (i.e., weight loss-focused) physical activity messages. Secondary purposes were to examine between condition differences on internalized weight bias and whether message ratings or internalized weight bias mediated effects of message type on objectively measured physical activity.Methods Adults of any self-identified gender who also self-identified as living in larger bodies were recruited through a variety of Obesity Canada channels including their newsletter and social media. The data from 54 adults (Mage = 49.9 years; 90.7% women) were analyzed. Participants completed pre-test measures (demographics and internalized weight bias), wore an accelerometer for one week then viewed eight images with condition-specific messages. This was followed with post-test measures (image ratings, thought listing, internalized weight bias) and one more week of accelerometer wear.Results The weight-neutral messages were rated more positively than the weight-centric messages but there were no between group differences in internalized weight bias nor in sedentary behavior, light physical activity, or moderate to vigorous physical activity.Discussion It is possible that participants were already interested in the topic of weight bias and possibly aware of the images used in this study, limiting the generalizability of the study. However, the results of this research, considered with the findings of other researchers who report health messages to be more motivating, indicate that focusing on weight is not recommended when promoting physical activity to people in larger bodies. Rather other benefits of being active should be highlighted.